EFFORTS TO IMPROVE READING SKILLS IN CHILDREN WITH DYSLEXIA THROUGH CONTENT MASTERY SERVICES USING PLAY THERAPY TECHNIQUES AT SDN 70/IV JAMBI - Hanipah; Rasimin Rasimin; Affan Yusra (SUJANA: Education and Learning Review, 2023)
This research is motivated by reading problems that often occur in students. The purpose of this study was to reveal how much the reading skills of dyslexic children at SDN 70/IV Jambi improved by using play therapy techniques through content mastery services. This research is a service action research (PTL). The subjects in this study were two fifth grade students and one sixth grade student at SDN 70/IV Jambi with a total sample of 3 students. The results of this study were seen from the observation sheet in seeing the increase in reading skills of dyslexic students. The results of this study explained that the percentage level of reading skills in cycle 1 reached 72% went well, in cycle 2 reached 85% went well and in the implementation of cycle 3 reached 92% went very well. this shows that the higher the percentage level, the more success will be achieved in carrying out service action research (PTL) at SDN 70/IV Jambi.